Pacific finance sector brief Nauru. (Metro Manila, Philippines Asian Development Bank, 2019)
Just over a decade ago, Nauru was a tax haven with hundreds of offshore banks registered in its finance sector. However, lenient banking regulations led to money-laundering and banking licenses were revoked. The Bank of Nauru was closed in 2006. The government recently reestablished banking services in the country, but financial limitations remain a major challenge. Nauru needs to continue efforts to strengthen its framework on anti-money laundering and combat the financing of terrorism, so that the country can reconnect to the international financial system.
Keywords: Finance -- Nauru; Industrial policy; Electronic books